1972
DOI: 10.1111/j.1469-8986.1972.tb00740.x
|View full text |Cite
|
Sign up to set email alerts
|

Sources of Information Which Affect Training and Raising of Heart Rate

Abstract: This study was concerned with the effects of cardiac information and reinforcement on raising heart rate (HR). The experiment consisted of a 3 × 2 design with three types of cardiac information and two reinforcement conditions. The cardiac information given to Ss consisted of instructions to control an internal response (no specific HR information), instructions to increase HR (specific HR information), or instructions to increase HR while hearing heart beats through earphones (augmented HR information). Exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1974
1974
1980
1980

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(18 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…In our study, instructions admittedly differed from those used in most studies of instructional set (12,13). Monotonous and repetitious, they may have been more forceful and suggestive, thus serving as a more potent and direct stimulus.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In our study, instructions admittedly differed from those used in most studies of instructional set (12,13). Monotonous and repetitious, they may have been more forceful and suggestive, thus serving as a more potent and direct stimulus.…”
Section: Discussionmentioning
confidence: 86%
“…A direct and specific response to the literal meaning of the instructions is not likely, while the intervention of associative imagery is suggested by interview data. Whatever the mechanism, the influence of instructional set on cardiovascular performance in the feedback paradigm has been demonstrated by other data (10)(11)(12)31). Whether mere awareness of the physiologic task at hand influences success has not been studied systematically, to our knowledge.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Also, their no-feedback but instructed group failed to exhibit any HR control at all. Bergman and Johnson (1972) and Stephens et al, among others, have shown that instructions constitute a sufficient condition for control of HR. One possible explanation is that Blanchard et al were using paid subjects and daily sessions which may have reduced subject motivation.…”
mentioning
confidence: 97%
“…Recently, investigators interested in human operant heart-rate conditioning have begun examining the role of an individual's proprioceptive awareness of automatic functioning in acquiring control over heart-rate changes (e.g., Bergman & Johnson, 1971;Blanchard, Young, & McLeod, 1972;McFarland, 1975;Sirota, Schwartz, & Shapiro, 1974). Other operant heart-rate conditioning studies have been reported in which an individual's awareness of the response-reinforcement contingencies has been examined by manipulating instructional set (e.g., Bergman & Johnson, 1972;McCanne & Sandman, 1975a). The latter studies have indicated that subjects informed of the specific reinforcement contingencies are able to produce larger operant heart-rate accelerations than subjects who are not informed of the contingencies.…”
mentioning
confidence: 99%